Ulnar nerve neuropathy caused by pathologic ossification: a case report - Vojtěch, Kunc; David, Kachlík; Ivan, Humhej (Surgical and radiologic anatomy, 2023)
PURPOSE: Cubital tunnel syndrome is a well-described entity with many reported etiologies and anatomical compression sites. Accessory ossicles of either traumatic or congenital origin might occur around the elbow joint. Only one case reporting such ossicles compressing the ulnar nerve exists in previous literature. We aim to present this entity with a detailed description of the patient history and treatment. CASE REPORT: We report a case of 30-year-old female presenting with classical signs of cubital tunnel syndrome-positive Wartenberg's and Froment's signs, hypoesthesia in the fourth and fifth finger with decreased finger duction strength but without gross hypotrophy of interosseous and hypothenar muscles. Tinel's sign was positive over the ulnar sulcus and an accessory ossicle was found on the elbow radiograph within the ulnar sulcus. The first signs of calcification in this patient were reported 6 years prior in a follow-up after the dislocation of her elbow joint following a bike accident. The EMG confirmed ulnar nerve neuropathy in the elbow area. The ossicle was extirpated, the ulnar nerve was decompressed in the ulnar sulcus in a standard manner and the symptoms quickly resolved. The patient has been regularly visiting our outpatient clinic for the next 12 years without any complaints considering her elbow and the ulnar nerve. CONCLUSION: This is a rare case of cubital tunnel syndrome caused by an accessory ossicle of traumatic origin. Simple bone extirpation with ulnar nerve release followed by anterior subcutaneous transposition is the recommended method of treatment. No report of congenital accessory bones causing ulnar nerve compression in the elbow exists in the literature.
Keywords: heterotopická osifikace; Elbow; loketní kloub; Ulnar Nerve; Adult; ženské pohlaví; Cubital tunnel syndrome; Humans; Ossification, Heterotopic; Cubital Tunnel Syndrome; Ulnar nerve neuropathy; syndrom kubitálního tunelu; Pathologic ossification; Elbow Joint; nervus ulnaris; dospělí; Accessory bones; Female; lidé; loket